2007
DOI: 10.1007/s12011-007-0056-2
|View full text |Cite|
|
Sign up to set email alerts
|

Zinc Distribution and Expression Pattern of ZnT3 in Mouse Brain

Abstract: To explore the relationship between the zinc distribution and zinc transporter 3 (ZnT3) mRNA expression in the mouse brain, zinc contents and its distribution were determined by synchrotron radiation x-ray fluorescence (SRXRF), and ZnT3 mRNA expression was examined by reverse-transcription polymerase chain reaction and in situ hybridization. The results showed that the zinc contents were not distributed evenly in various brain tissues. The zinc contents in cerebral cortex and hippocampus were nearly 5-10 times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…In contrast, only labile, vesicular Zn is visualized by histochemical, histofluorescent [7,15] and immunofluorescent staining methods [34,39,44]. Since the labile Zn pool comprises only ~5% [16] to ~20% of total Zn [7], plasticity associated changes in Zn concentration may be below the detection limits of XFI due to the relatively small change relative to the total Zn level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, only labile, vesicular Zn is visualized by histochemical, histofluorescent [7,15] and immunofluorescent staining methods [34,39,44]. Since the labile Zn pool comprises only ~5% [16] to ~20% of total Zn [7], plasticity associated changes in Zn concentration may be below the detection limits of XFI due to the relatively small change relative to the total Zn level.…”
Section: Discussionmentioning
confidence: 99%
“…Zn can be visualized using various staining techniques. Histochemical [7] and immunofluorescent staining methods [34,39,44] visualize primarily labile Zn. However, these methods also stain other divalent metal cations, including Ca +2 [10,38,47], which can overestimate the role of Zn in brain plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, it was reported that Zn-enriched cortical regions detected by XFI correspond to ZnT3 rich terminal boutons (Linkous et al, 2008). Secondly, coincident accumulation of Zn in the vesicles with a zinc-specific pump called ZnT3 has been shown via juxtaposition of histochemically, histo(cyto)fluorescently and immunofluorescently stained brain specimens (Lee et al, 2011; Palmiter et al, 1996; Shen et al, 2007). Although vesicular Zn, the “labile” Zn pool detected by histofluorescence methods, accounts for only approximately 23% of the total Zn in the cortex (Cole et al, 1999), it is considered to represent 95% of the entire histofluorescently reactive Zn pool (Lee et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of free zinc ions in the extracellular space of healthy brain tissue is in the range of 1 to 10 nM, and the cytosolic zinc concentration is in the picomolar range (Frederickson et al 2005). But in the proximity of axon terminals, zinc rises to micromolar levels following release from synaptic vesicles that contain zinc in the millimolar concentration (Shen et al 2007;Linkous et al 2008). Synaptic zinc is involved in signal transmission/transduction across synapses and therefore modulates synaptic transmission and plasticity (Frederickson et al 2005;Besser et al 2009).…”
Section: Zinc In Alzheimer's Diseasementioning
confidence: 99%